2004
DOI: 10.1111/j.1471-4159.2004.02797.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydroxylase phosphorylation: regulation and consequences

Abstract: The rate-limiting enzyme in catecholamine synthesis is tyrosine hydroxylase. It is phosphorylated at serine (Ser) residues Ser8, Ser19, Ser31 and Ser40 in vitro, in situ and in vivo. A range of protein kinases and protein phosphatases are able to phosphorylate or dephosphorylate these sites in vitro. Some of these enzymes are able to regulate tyrosine hydroxylase phosphorylation in situ and in vivo but the identity of the kinases and phosphatases is incomplete, especially for physiologically relevant stimuli. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
569
3
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 417 publications
(594 citation statements)
references
References 115 publications
(353 reference statements)
11
569
3
11
Order By: Relevance
“…2B). The activity of TH can be modulated by phosphorylation, and phospho-serine 40 TH (pSer40 TH) represents an active form of the enzyme (28). We found that, in Foxa1/2 cKO mice, there was also a small but significant reduction in the amount of pSer40 TH, normalized to the total amount of TH ) Quantification of FOXA1/2 colocalization with TH+ neurons, and efficiency of deletion is shown in the graph (C) (proportion of TH+ neurons that coexpresses FOXA1/2; control VTA = 95.8% ± 2.9, control SNc = 95.8% ± 3.6; Foxa1/2 cKO VTA = 10.4% ± 3.6*, Foxa1/2 cKO SNc = 1.4% ± 1.6*; n = 3; mean ± SEM; *P < 0.001 vs. control, t test).…”
Section: Resultsmentioning
confidence: 99%
“…2B). The activity of TH can be modulated by phosphorylation, and phospho-serine 40 TH (pSer40 TH) represents an active form of the enzyme (28). We found that, in Foxa1/2 cKO mice, there was also a small but significant reduction in the amount of pSer40 TH, normalized to the total amount of TH ) Quantification of FOXA1/2 colocalization with TH+ neurons, and efficiency of deletion is shown in the graph (C) (proportion of TH+ neurons that coexpresses FOXA1/2; control VTA = 95.8% ± 2.9, control SNc = 95.8% ± 3.6; Foxa1/2 cKO VTA = 10.4% ± 3.6*, Foxa1/2 cKO SNc = 1.4% ± 1.6*; n = 3; mean ± SEM; *P < 0.001 vs. control, t test).…”
Section: Resultsmentioning
confidence: 99%
“…Ser31 and Ser40 of TH are believed to be directly involved in DA synthesis because increases in the phosphorylation of TH at these two sites enhance the catalytic activity of TH (Colby et al, 1989;Dunkley et al, 2004). Compared with control animals, AMPH self-administration did not change the expression of TH, but significantly reduced the level of TH phosphorylation at serine 31 (N ¼ 5-6, two-tailed unpaired t-test, t 9 ¼ 3.054, Po0.05) and serine 40 (t 9 ¼ 2.427, Po0.05) as shown in Figure 3.…”
Section: Amph Self-administration Reduced D2/d3 Autoreceptor Functionmentioning
confidence: 99%
“…This result is consistent with previous work where attempts to demonstrate the phosphorylation of hTH2 Ser 35 in intact human neuroblastoma cells (prelabeled with 32 P i , treated with veratridine, forskolin, or phorbol ester, immunoprecipitated with isoform-specific antibodies, trypsinized, and analyzed by HPLC with radiochemical detection) indicated, rather, that hTH2 Ser 35 was essentially not phosphorylated under any of the conditions. 3 Effect of ERK Phosphorylation on the Human TH Isoforms-We examined the effect of ERK phosphorylation on the rate of activation of the dopamine-bound human TH isoforms by PKA. The data is shown in Fig.…”
Section: Determination Of Th Activity and The Incorporation Of Radioamentioning
confidence: 99%
“…14.16.2] is the rate-limiting enzyme in the biosynthesis of the catecholamines dopamine, noradrenaline, and adrenaline (1). Short term regulation of TH is accomplished by dynamic changes in the phosphorylation state of the enzyme (2,3). Although four serine residues have been shown to be phosphorylated in TH, only three of these serine residues (Ser 19 , Ser 31 , and Ser 40 ) are regulated in vivo (4).…”
mentioning
confidence: 99%